2017
DOI: 10.1021/acs.jpcb.6b12146
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Dynamics and Proton Transfer in Diethylaminohydroxyflavone

Abstract: 4'-N,N-Diethylamino-3-hydroxyflavone (DEAHF) exhibits dual fluorescence in most solvents as a result of a rapid excited-state intramolecular proton transfer reaction. The high sensitivity of its dual emission to solvent polarity and hydrogen bonding make DEAHF of interest as a ratiometric fluorescence sensor. In addition, prior work has suggested that the rate of this proton transfer should depend on solvent relaxation in an unusual manner. It has been proposed that rapid solvation of the initially excited rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 34 publications
3
34
0
Order By: Relevance
“…For this reason, the assignment of the fast processes having time constants in the range 7-10 ps, to the forward ESIPT reaction is not justified physically in the article. Support of our arguments one can find in [14] where the authors clearly demonstrate the presence of T * form in instant spectra of 4′-N, N-diethylamino-3-hydroxyflavone (DMAHF) sample even at times shorter 0.1 ps that confirms too low time resolution of the device used in the article of Szalai et al [13] The reliable time measurements with picosecond resolution <10-100 ps must be performed using femtosecond excitation pulses and up conversion technique for detection of emission kinetics [7].…”
Section: Vladimir I Tominsupporting
confidence: 86%
See 1 more Smart Citation
“…For this reason, the assignment of the fast processes having time constants in the range 7-10 ps, to the forward ESIPT reaction is not justified physically in the article. Support of our arguments one can find in [14] where the authors clearly demonstrate the presence of T * form in instant spectra of 4′-N, N-diethylamino-3-hydroxyflavone (DMAHF) sample even at times shorter 0.1 ps that confirms too low time resolution of the device used in the article of Szalai et al [13] The reliable time measurements with picosecond resolution <10-100 ps must be performed using femtosecond excitation pulses and up conversion technique for detection of emission kinetics [7].…”
Section: Vladimir I Tominsupporting
confidence: 86%
“…As was shown [14,[17][18][19] the thermodynamic equilibrium distribution obeys to the Boltzmann law: is the statistical weight, k is the Boltzmann constant, T is the absolute temperature.…”
Section: Vladimir I Tominmentioning
confidence: 91%
“…Based on DFT//TDDFT/B3LYP/6‐31G(d) level in toluene solvent, we construct the PESs for the Ia system in both S 0 and S 1 states with fixing both O1―H2 and O4―H5 bond lengths. Herein, we want to mention that although previous work has reported that the TDDFT theoretical level might not provide the sufficiently accurate ordering of closely spaced excited states, theoretical results have shown the reliability of this method to offer qualitative energetic pathways for ESIPT behaviors . Specifically, the constructed PESs of both S 0 and S 1 states are through fixing O1―H2 and O4―H5 ranged from 0.9 to 2.1 Å in step of 0.1 Å (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Rumble et al . recently studied 4′‐N,N‐diethylamino‐3‐hydroxyflavone, a dual fluorescence emitting molecule, using femtosecond kerr‐gated emission spectroscopy . To investigate the solvation effect they have studied the molecule in propylene carbonate ‐ acetonitrile mixture, which have variable solvation time at different composition but the polarity remains almost same .…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the solvation effect they have studied the molecule in propylene carbonate ‐ acetonitrile mixture, which have variable solvation time at different composition but the polarity remains almost same . They have used a ESIPT‐solvation coupling model, previously proposed by Kimura et al ., and established that the timescale of ESIPT process changes inversely with the solvation time of the mixture . Polar protic solvents can also directly take part in the proton transfer process, which has been previously explored by Douhal and co‐workers in the nanocavity of cyclodextrin .…”
Section: Introductionmentioning
confidence: 99%